The prevalence of autonomic neuropathy in a selected group of male diabetics - Rajakanthan, K.; Weerasooriya, P.; Gunatilleke, N.; Nanayakkara, S.; Jayasinghe, S.; Sheriff, M.H.R. (My University, 1991)
Autonomic neuropathy in diabetes is often asymptomatic and diagnosed only by screening tests. It is associated with a poor prognosis and a high risk of cardiovascular mortality during anaesthesia. We studied the prevalence of AN in selected group of 50 diabetic males aged (24-77 years (mean 48 years) white diabetes of more than 5 years. (mean 9.6 years). 31 patients (62%) were being treated with lente insulin and the rest were on oral medication. Standard autonomic reflexes were used to identify autonomic dysfunction. 30 patients (60%) had autonomic dysfunction. 10 patients (20%) had early parasympathetic dysfunction. 13 (26%) had difite parasympathetic dysfunction and 5 (10%) had combined sympathetic and parasympathetic dysfunction. Two (4%) had an atypical pattern. According to most series from the west to 40% of adult diabetics have abnormal cardiovascular autonomic function tests. The reason for a higher incidence of autonomic dysfunction found in our series is unclear. Poor control of diabetes and racial differences in susceptibility to autonomic neuropathy may be important factors. Further studies are needed to confirm these findings.